A New Cause of Male Infertility After Cisplatin Exposure: The Effect of Cisplatin on Y Chromosomes - ŞİMŞEK, FERRUH; ÖZYÜREK, MUSTAFA (ELSEVIER SCIENCE INC, 2009)
OBJECTIVES To investigate the impact of cisplatin (CP) on the testes-specific protein, Y-linked (TSPY) gene situated on the Y chromosome. METHODS The control group consisted of 10 rats. Group IIA consisted of 15 rats that underwent orchiectomy and received three cycles of 1 mg/kg, 2.5 mg/kg, or 5 mg/kg CP. Group IIB was,exposed to the same doses of three cycles of chemotherapy but was examined after 3 months of chemotherapy. Group III was exposed to the same doses of chemotherapy without initial orchiectomy. Reverse transcriptase polymerase chain reaction for TSPY messenger ribonucleic acid (mRNA) and immunohistochemical staining for histone 213 were per-formed on the testes. Results were evaluated by one-way analysis of variance. RESULTS Compared with the controls, the expression of TSPY mRNA in Group IIA after exposure to 1 mg/kg CP did not change; however, MRNA levels after exposure to 2.5 mg/kg and 5 mg/kg CP were decreased by 40% and 78%, respectively. In Group III after exposure to the same doses of CP, mRNA levels decreased by 30%, 87.5%, and 88%, respectively. The expression of TSPY was at normal levels except in rats that received 5 mg/kg CP in Group IIB. Immunohistochemical study revealed that histone 213 expression was decreased in a dose-dependent manner. None of the rats from any of the groups died during the study period. CONCLUSIONS Decreased TSPY expression after CP exposure might be another mechanism for male infertility. UROLOGY 73: 1145-1149, 2009. (C) 2009 Elsevier Inc.
Keywords: TESTICULAR FUNCTION; GONADAL-FUNCTION; CHEMOTHERAPY; CANCER; EXPRESSION; ORGANIZATION; DRUGS